Aktivitas Wanita Tani dalam Agroindustri Opak dan Kontribusinya terhadap Pendapatan Rumah Tangga Petani (Studi Kasus Pada Wanita Tani Desa Cikurubuk Kecamatan Buahdua Kabupaten Sumedang): Analisis Usaha Tani - Edang Juliana; Nataliningsih (Agrivet : Jurnal Ilmu-Ilmu Pertanian dan Peternakan (Journal of Agricultural Sciences and Veteriner), 2022)
ABSTRACT This study aims to describe the activities of women farmers in the opak agroindustry, their income and their contribution to household income in Cikurubuk Village, Buahdua District, Sumedang Regency. The research method used is a survey with a census sampling technique consisting of 10 female farmers as samples. The purpose of this study was to determine : 1) the amount of expenses incurred by opak craftsmen in Cikurubuk Village, Buahdua District, Sumedang Regency, 2) The amount of opak agroindustry income per month in Cikurubuk Village, Buahdua District, Sumedang Regency, 3) Contribution monthly income of opak agroindustry to family income in Cikurubuk Village, Buahdua District, Sumedang Regency. The method used in this research is a survey of opak craftsmen women farmers in the area of ​​Cikurubuk Village. Meanwhile, data processing uses cost, revenue, income, and contribution analysis of opak agroindustry. The results of the study show: 1) The average total cost incurred by opak craftsmen in Cikurubuk Village, Buahdua District on opak agroindustry per one production process is Rp. 813.168.-; 2) The average total income earned by the opak craftsmen in Cikurubuk Village in the opak agro-industry per one production process is Rp. 458532,-; 3) The average income contribution of respondents from the opak agroindustry is 55,34 % (Rp 3.668.256,-).